Jumping through the hoops: Barriers and other ethical concerns regarding the use of psychiatric electroceutical interventions. (July 2022) - Cabrera, Laura Y.; Miller, Maryssa M.C.; Achtyes, Eric D.; McCright, Aaron M.; Bluhm, Robyn
Highlights: Access limitations are important barriers that cut across all PEIs. Stigma continues to be a key attitudinal barrier, in particular for ECT. Informed consent was perceived as a key ethical issue around the use of PEIs. Abstract: Stakeholders' perceptions of barriers to and other ethical concerns about using psychiatric electroceutical interventions (PEIs), interventions that use electrical or magnetic stimuli to treat psychiatric conditions like treatment-resistant depression (TRD), may influence the uptake of these interventions. This study examined such perceptions among psychiatrists, patients with depression, and members of the public. We conducted semi-structured qualitative interviews with 16 members of each group to examine their views on practical barriers and ethical concerns. We used qualitative content analysis to identify relevant themes, and compared findings across stakeholder groups. Access limitations to the interventions, including cost and availability of the interventions, cut across all PEIs—including those that are still experimental, and were raised by all groups. Most participants across all groups raised concerns about informed consent, in terms of receiving adequate, appropriate, and understandable information. Our results suggest that these three stakeholder groups perceive similar structural and attitudinal barriers to, and have similar ethical concerns about, using PEIs for TRD. These results identify key issues that must be addressed for the full potential of PEIs to be realized. Future research with larger samples will help to better understand how to address these barriers to treatment for individuals with TRD.